Improving the ozone retrieval accuracy by minimizing the asynchronous offset in differential absorption lidar systems - Zhao, Duliang; Tang, Chao; Meng, Xiangrui; Li, Shili; Wang, Yanfei; Du, Zhengting; Yu, Longbao; Jiang, Shan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
The differential absorption lidar (DIAL) has been proposed as an effective method for detecting ozone in the atmosphere. An important factor affecting its detecting precision is the asynchronous offset between backscattered signals at different wavelengths. Recently, a DIAL was built by our group, and the impact of the asynchronous offset was tested and studied. The simulation results show that the measurement error caused by the offset is negatively correlated with the altitude. Meanwhile, the offset has an additional effect in areas with sharp ozone concentration changes. Comparative experiments were carried out by our DIAL system and an airborne atmospheric monitoring system in the Nanjing test site. The results show that a 15 m offset in DIAL led to serious errors in retrieval results. These errors are inversely related to the detection altitude and reach up to 13 ppb, which is consistent with the results from simulations. After controlling the relative position of the backscattered signal to minimize the asynchronous offset, the maximum error was reduced to 2 ppb. Then the optimized DIAL was used for 48-hour continuous observation with a proven ozone analyzer. It shows that the optimized DIAL has high detecting accuracy and stability as point-fixed instruments.
Optica Applicata, Vol. 54, 2024, nr 2, s. 231-243
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; lidar; differential absorption; asynchronous offset; ozone